The influence of vascularization of transplanted processed allograft nerve on return of motor function in rats. Issue 2 (30th December 2014) - Giusti, Guilherme; Lee, Joo‐Yup; Kremer, Thomas; Friedrich, Patricia; Bishop, Allen T.; Shin, Alexander y.
Abstract : Processed nerve allografts have become an alternative to repair segmental nerve defects, with results comparable with autografts regarding sensory recovery; however, they have failed to reproduce comparable motor recovery. The purpose of this study was to determine how revascularizaton of processed nerve allograft would affect motor recovery. Eighty‐eight rats were divided in four groups of 22 animals each. A unilateral 10‐mm sciatic nerve defect was repaired with allograft (group I), allograft wrapped with silicone conduit (group II), allograft augmented with vascular endothelial growth factor (group III), or autograft (group IV). Eight animals from each group were sacrificed at 3 days, and the remaining animals at 16 weeks. Revascularization was evaluated by measuring the graft capillary density at 3 days and 16 weeks. Measurements of ankle contracture, compound muscle action potential, tibialis anterior muscle weight and force, and nerve histomorphometry were performed at 16 weeks. All results were normalized to the contralateral side. The results of capillary density at 3 days were 0.99% ± 1.3% for group I, 0.33% ± 0.6% for group II, 0.05% ± 0.1% for group III, and 75.6% ± 45.7% for group IV. At 16 weeks, the results were 69.9% ± 22.4% for group I, 37.0% ± 16.6% for group II, 84.6% ± 46.6% for group III, and 108.3% ± 46.8% for group IV. The results of muscle force were 47.5% ± 14.4% for group I, 21.7% ± 13.5% for group II, 47.1% ± 7.9% for group III, and 54.4% ± 10.6% for group IV. The use of vascular endothelial growth factor in the fashion used in this study improved neither the nerve allograft short‐term revascularization nor the functional motor recovery after 16 weeks. Blocking allograft vascularization from surrounding tissues was detrimental for motor recovery. The processed nerve allografts used in this study showed similar functional motor recovery compared with that of the autograft. © 2014 Wiley Periodicals, Inc. Microsurgery 36:134–143, 2016.